Relation between Breast Cancer and High Glycemic Index or Glycemic Load: A Meta-analysis of Prospective Cohort Studies. Issue 1 (2nd January 2016) - Mullie, Patrick; Koechlin, Alice; Boniol, Mathieu; Autier, Philippe; Boyle, Peter
Abstract : Breast cancer is the commonest form of cancer in women worldwide. It has been suggested that chronic hyperinsulinemia associated with insulin resistance plays a role in breast cancer etiology. To test the hyperinsulinemia hypothesis, a dietary pattern associated with a high glycemic index and glycemic load, both proxies for chronic hyperinsulinemia, should be associated with an increased risk of breast cancer. A meta-analysis restricted to prospective cohort studies was undertaken using a random effects model with tests for statistical significance, publication bias and heterogeneity. The metric for analysis was the risk of breast cancer in the highest relative to the lowest glycemic index and glycemic load dietary pattern. A dietary pattern with a high glycemic index was associated with a summary relative risk (SRR) of 1.05 (95% CI: 1.00, 1.11), and a high glycemic load with a SRR of 1.06 (95% CI: 1.00, 1.13). Adjustments for body mass index [BMI], physical activity and other lifestyle factors did not influence the SRR, nor did menopausal status and estrogen receptor status of the tumor. In conclusion, the current evidence supports a modest association between a dietary pattern with high glycemic index or glycemic load and the risk of breast cancer.